2006
DOI: 10.1056/nejmoa052643
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fingolimod (FTY720) for Relapsing Multiple Sclerosis

Abstract: In this proof-of-concept study, fingolimod reduced the number of lesions detected on MRI and clinical disease activity in patients with multiple sclerosis. Evaluation in larger, longer-term studies is warranted. (Clinicaltrials.gov numbers, NCT00333138 [core study] and NCT00235430 [ClinicalTrials.gov] [extension].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
822
2
20

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 985 publications
(875 citation statements)
references
References 33 publications
31
822
2
20
Order By: Relevance
“…FTY720 (fingolimod), when phosphorylated by sphingosine kinase, functions as an S1P receptor agonist and targets four (out of the five) S1P receptors. FTY720 interferes with the exit of lymphocytes from lymph nodes, and therefore attenuates autoimmune disease (for example, multiple sclerosis) [106][107][108] , organ rejection in transplantation, and is under consideration for other inflammatory and allergic conditions 27,109 . S1P1-specific agonists (SWE2871; REF.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…FTY720 (fingolimod), when phosphorylated by sphingosine kinase, functions as an S1P receptor agonist and targets four (out of the five) S1P receptors. FTY720 interferes with the exit of lymphocytes from lymph nodes, and therefore attenuates autoimmune disease (for example, multiple sclerosis) [106][107][108] , organ rejection in transplantation, and is under consideration for other inflammatory and allergic conditions 27,109 . S1P1-specific agonists (SWE2871; REF.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…The regions of interest (ROI) were manually traced by a single tracer (EB) with a mouse-driven cursor using the interactive public domain software program AMIRA, which displays all three planes simultaneously (Kappos et al, 2006). The boundaries of the hippocampus were identified including the subiculum, cornu ammonis (hippocampus proper), and the dentate gyrus.…”
Section: Manual Segmentation Of Hippocampus Volumementioning
confidence: 99%
“…However, previous studies using the same software on data sets comprising over 1000 MRI scans showed a very high inter-rater reliability (Kappos et al, 2006). The researcher who traced the hippocampus was blind to the group at any time of the study.…”
Section: Manual Segmentation Of Hippocampus Volumementioning
confidence: 99%
“…2,3 Clinical studies have demonstrated a side effect profile of 1 that includes cardiovascular effects (transient bradycardia, sustained blood pressure elevation) as well as a decline in pulmonary function. 4 In rodent studies, S1P 3 activity was shown to play a role in some of the observed acute toxicity of nonselective S1P receptor agonists, including bradycardia, hypertension, and bronchoconstriction. 5,6 As agonism of S1P 3 does not appear to contribute to efficacy, the identification of S1P 1 agonists sparing of S1P 3 has been a primary emphasis of many research programs in this area.…”
mentioning
confidence: 99%